THE ROLE OF HYPNOPARENTING IN THE TREATMENT OF EARLY CHILDHOODâS TEMPER TANTRUM - Astuti, Henny Puji (Indonesian Journal of Early Childhood Education Studies, 2012)
At the age of two to fourÂ  years of aÂ  childs emotional characteristics emerged withoutbursts or temper tantrums. Temper tantrums are flare-ups occur suddenly, without planned. A method to overcome the childs temper tantrums is by using hypnoparenting. HypnoparentingÂ Â  infuse positive suggestionÂ Â  into childs unconscious mind, so that the child have a positive personal that establishing a good pattern of behavior. This study aims to examine and obtain empirical data on the differences between the behavior of the child temper tantrums before and after havinghypnoparenting treatment. Hypothesis in this study is a difference between the behavior of the child temper tantrums before and after having the hypnoparenting treatment. In fact, tempertantrum still happens on the child above 4 years old.Â Â  i have apply the method ofÂ  hypnoparenting in handling childs tempertantrum above 4 years old. i have provide training of hypnoparenting to parents. The training held to teach a subjectmatter of hypnoparenting to the parents for a week. Thereafter, the parents apply hypnoparenting inÂ  early childhoodÂ  forÂ  21Â  daysÂ  andÂ  theÂ  teacherÂ  helpÂ  meÂ  toÂ  observeÂ  andÂ  recordÂ  the tempertantrum behavior in the classroom before and after having hypnoparenting treatment. The number of subjects in this study is 33 childrens. They are four to six years old. The measurement scale in this study is Temper Tantrum Scale. Theresult of Paired Samples T-test shows that there is significant difference of the childâs tempertantrum behavior between before and after having hypnoparenting treatment, t = -5.611 with p = 0.00. This study explains that there is a difference in the behavior ofÂ  childs tempertantrum before and after having hypnoparenting treatment. The behavior of childs tempertantrum after having hypnoparenting treatment lower than before.